UTILIZAÇÃO DE RESÍDUOS DE MADEIRA CANDEIA (Eremanthus erythropappus) COMO ANTIOXIDANTE PARA BIODIESEL - Scaburi, Gustavo Rinaldo (2017)
With the estimates of depletion and the awareness about environmental issues, the less polluting energy sources are sought and as effective as those derived from petroleum. Thus, biodiesel, which is derived from renewable resources of energy and that answers the performance issue close to diesel, is gaining more and more prominence. However, it is obtained from unsaturated fatty acids contained in vegetables, which accelerates the oxidation process of this biofuel. Aiming to combat this, synthetic antioxidants are added, that despite their efficiency, present toxicity to the population and the environment. Therefore, the objective of the study is to verify the feasibility of using natural antioxidants obtained from the agro-industrial residue of candeia, citric acid and ascorbic acid. The extraction of the compounds from the residue occurred by acid way (HCl solution), where it was transferred approximately 20% of the initial mass to the solution that was diluted and used in the biodiesel washing step, while the citric acid and ascorbic acid were added directly in the samples. A simplex-centroid experimental design was performed for three components. To perform the accelerated oxidation tests, the 873 Biodiesel Rancimat-Metrohm® method was used. The other techniques used to evaluate the parameters of biodiesel were through Incoterm® densimeter, for the specific mass, ERASPEC® equipment for determination of the ester content, Pensky-Martens for flash point testing, the pH was taken by pHmetro DIGIMED® model DM-20, the water content was given by the Karl Fischer method (889 Coulometer da Metrohm®), finally, color and appearance were evaluated by visual analysis. Additive biodiesel with only extract residue of candeia (1g / L) presented an oxidative stability of 7,5267 ± 0,722 hours. For the mixture with 0,5 g/L of residue and 0,05% m/V of citric acid the oxidative stability time was 11,8300 ± 0,0781 hours, while for the mixture with 0,5 g/L of residue and 0,05% m/V of ascorbic acid the time was 12,3300 ± 0,6056 hours, both surpassing the limits imposed by the brazilian (8h) and european (6h) standards, furthermore, the combination of candeia + ascorbic acid increased by 296% the oxidation stability time compared to biodiesel without the addition of antioxidants.